CONTINUING EDUCATION OF MATHEMATICS TEACHERS: ‘REFLECTIONS ON THEIR TEACHING PRACTICE’ - Lima Cangirana de Jesus, Dináurea; Wendel Santana Coêlho, Márcio (Revista Gênero e Interdisciplinaridade, 2022)
The investigations about continuing education in the school environment highlight the importance of appreciating the work of the teaching professional. Based on this assumption, this article is a text whose objective is to show the contribution and importance of continuing education for teaching practice. Seen in this way, the need for specific training in the area of ​​mathematics is one of the reasons why teachers feel the need for this qualification, since it enables a better performance of pedagogical work, and, consequently, a quality teaching, contemplating the student with a mathematics that goes beyond the walls of the school, and presents them with a new and broader vision of the study of mathematics. In view of the above, this study presents a bibliographic review providing a more intimate view of the educational reality, as well as the teaching-learning process.